Pelaksanaan Model Pembelajaran Make A Match Pada Mata Pelajaran PAI dalam Meningkatkan Hasil Belajar Siswa - Alviondra, Dion; Rahman, Rini (An-Nuha, 2024)
One of the problems in learning Islamic Religious Education (PAI) is that students are less active or lack of enthusiasm in learning. To overcome this problem, PAI teachers have used the Make A Match learning model in 2022. This study aims to describe the implementation of the Make A Match learning model in PAI learning in class V B SDN 20 Kalumbuk Padang City. This study uses a qualitative method with a descriptive qualitative research type. The data source of this study was informants through interviews with Islamic Religious Education teachers and students of class V B SDN 20 Kalumbuk. To obtain research data, the researcher used interview and observation guidelines as research instruments. The data collection techniques used were observation, interviews, and documentation. While the data analysis techniques used were data reduction, data presentation, and drawing conclusions. Overall, the results of the research analysis showed that there were three stages, namely the implementation stage in the preliminary activities in the form of teachers opening learning by greeting, greeting and checking student attendance, providing motivation, informing the material, namely about Surah Al-Ma'un, conveying learning objectives, explaining the activities to be carried out, and providing material reinforcement to students. The implementation of core activities is adjusted to the syntax of the Make A Match learning model. As well as closing activities, namely student assessments, teachers and students conclude learning, close learning with greetings and prayers.